GAMBARAN PERILAKU PETUGAS KESEHATAN DALAM KEGIATAN INISIASI MENYUSU DINI (IMD) DI RSI IBNU SINA DAN RSUD DR. ADNAAN WD DI KOTA PAYAKUMBUH TAHUN 2017 - Famy Bisyawqi; Fitri Ardiani; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The infant and child mortality rate of health development of a country and the quality of life of the communit. One effort that can be done to reduce infant mortality rate is through the promotion of eksklusif breastfeeding to infants for 6 months. To support the promotion, one way that can be done is by applying an early breastfeeding initiation program which is giving breast milk to the baby immediately within 1 hour after birth. This study aims to determine the description of the behavior of health workers in the activities of Early Breastfeeding Initiation in RSI Ibnu Sina and RSUD dr. Adnaan WD in Payakumbuh. The type of this research is descriptive quantitative by using cross sectional design. The population of 43 people and all the population sampled (total sampling). Primary data include knowledge, attitudes and actions obtained by interview using questionnaires. Data on the number of early breastfeeding initiation and number of births were ontained from hospital documentation. The results showed that overall behavior of health workers in Early Breastfeeding Initiation activities has been included in the category either with knowledge level that is equal to 83,7%, attitude that is equal to 79,1% and action equal to 69,8% but health worker always doing early breastfeeding initiation activity is only 30,2%. Characteristics of health workers consisting of age, type of education, duration of work and IMD training can not affect health workers in performing IMD activities. Good knowledge and positive attitudes will not always bring good action in the execution of IMD activities, because an action will be possible if conditions and conditions support. It is therefore desirable for the hospitals to require health workers to deliver IMD to every newborn infant with no medical indication that could impede IMD implementation and to give strict sanction to those who do not carry out the activity and to the health officer to further improve the implementation the activity of the IMD in each newborn if there is no medical consideration that can be a hindrance to the implementation of the activity. Keywords: behavior, health officer, early breastfeeding initiation and exclusive breastfeeding